Medicinal leaf knowledge of the five Dayak Ethnic Groups in West Kalimantan, Indonesia - MARKUS IYUS SUPIANDI; SITI ZUBAIDAH; SUSRIYATI MAHANAL (Society for Indonesian Biodiversity, 2026)
Abstract. Supiandi MI, Zubaidah S, Mahanal S. 2026. Medicinal leaf knowledge of the five Dayak Ethnic Groups in West Kalimantan, Indonesia. Biodiversitas 27 (2): d270215. https://doi.org/10.13057/biodiv/d270215. The Dayak community in West Kalimantan, Indonesia, comprises 151 sub-ethnic groups, including the Iban, Tamambaloh, Jangkang, Limbai, and Linoh. These groups rely heavily on plant leaves for traditional medicine, transmitting their knowledge orally across generations. However, researchers have not adequately documented this knowledge in scientific literature. This study documents and analyzes the diversity of medicinal leaf species utilized by five Dayak Sub-ethnic Groups in West Kalimantan, Iban, Tamambaloh, Jangkang, Limbai, and Linoh, to preserve and promote their ethnobotanical heritage. Data were collected through structured interviews, participatory observation, and field documentation with local healers and community elders. The team identified plant species through an online platform, verified them with botanists, and organised the findings systematically in tables and figures. The analysis recorded 84 species belonging to 41 plant families. The Lamiaceae family contributed the highest number of species. Community members used these plants primarily to treat severe and chronic conditions, including cancer, diabetes mellitus, cardiovascular disorders, liver diseases, and kidney problems. The Iban, Tamambaloh, Jangkang, Limbai, and Linoh Dayak Sub-ethnic Groups actively preserve rich ethnobotanical knowledge centered on plant leaves. This study underscores the significance of integrating traditional medicinal knowledge into biodiversity conservation and sustainable development efforts, aligning with SDG 3 (Good Health and Well-being) and SDG 15 (Life on Land).